Should Charitable and Political Donations Benefit from Similar Tax Treatments? Evidence from a Survey Experiment - Julia Cagé; Malka Guillot; Yuchen Huang (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
In many countries, both charitable and political donations benefit from generous – and often similar – tax incentives. While a large literature has studied the tax-price elasticity of charitable giving, little is known about political donations. Using a large-scale survey experiment (N = 12,600), we investigate the relative efficiency of different tax schemes in fostering political and charitable donations. We document that repealing the existing non-refundable income-tax credit decreases charitable donations but not political donations, pointing toward greater fiscal incentives behind charitable giving. We next show that, conditional on giving, matching – where the government matches individual donations at a fixed rate – increases both political and charitable giving, but that it decreases the probability of giving to charities at the extensive margin. Finally, using a Principal Component Analysis (PCA) and generic machine learning, we document important dimensions of heterogeneity, and discuss the policy implications of our findings.
Keywords: H24; H31; L38; 330; charitable giving; political donations; tax incentives